Mobile Augmented Reality Prototype for the Manufacturing of an All-Terrain Vehicle - Vergara Villegas, Osslan Osiris (Springer, 2018)
In this chapter, a mobile augmented reality prototype to support the process of manufacturing an all-terrain vehicle (ATV) is presented. The main goal is assisting the automotive industry in the manufacturing process regarding vehicle design and new model’s introduction; in addition, the activities of training and quality control can be supported. The prototype is composed of three main stages: (a) welding inspection, (b) measuring of critical dimensions inspection, and (c) mounting of virtual accessories in the chassis. A set of 3D models and 2D objects was used as virtual elements related to augmented reality. The prototype was tested regarding usability in a real industrial stage by measuring the scope of markers’ detection and by means of a survey. The results obtained demonstrated that the prototype is useful for the manufacturing of an ATV.